Assessing the toxicity of the "inert" safener benoxacor toward Chironomus riparius: Effects of agrochemical mixtures. (22nd June 2017) - Bolyard, Kasey; Gresens, Susan E.; Ricko, Allison N.; Sivey, John D.; Salice, Christopher J.
Abstract: The environmental effects of safeners, agrochemicals that protect crops from herbicide toxicity, are largely unknown, perhaps because they are classified as inert ingredients. We assessed the toxicity to larvae of Chironomus riparius of 1) the dichloroacetamide safener benoxacor; 2) its degradation product, monochloro‐benoxacor; 3) the herbicide with which benoxacor is paired, S ‐metolachlor; and 4) a mixture of S ‐metolachlor + benoxacor. Under iron‐reducing conditions, benoxacor can undergo reductive dechlorination, producing monochloro‐benoxacor. To simulate iron‐reducing conditions, we prepared benthic microcosms containing an iron‐rich silt–clay sediment amended with cellulose. Larval C. riparius were exposed to single chemicals via spiked sediment at nominal concentrations ranging from 0.01 to 100 mg/kg. Concentrations of a 1:1 mixture of safener and herbicide ranged from 0.02 to 200 mg/kg. Kinetic modeling of microcosm aqueous‐phase concentrations indicated that benoxacor transformed with a half‐life of 12 d. Cox proportional hazard models of time to emergence during 28‐d experiments showed that females had a lowest‐observed‐effect concentration (LOEC) for benoxacor at 1 mg/kg, whereas their LOEC for monochloro‐benoxacor was 0.1 mg/kg. For males, the LOEC for all treatments was 100 mg/kg (200 mg/kg for the mixture). Synergistic effects of the mixture were observed only in females, with a LOEC of 0.2 mg/kg. These results suggest that benoxacor presents a low toxicity risk to C. riparius in environmental systems; however, the possibility of synergistic effects between benoxacor and S ‐metolachlor merits further investigation. Environ Toxicol Chem 2017;36:2660–2670. © 2017 SETAC